Economic growth and poverty reduction: measurement issues using income and non-income indicators - Stephan Klasen (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2006)
This paper addresses two issues concerning the measurement of pro-poor growth, a central concept for sustainable poverty reduction in developing countries. First, it attempts to clarify the debates about the definition and measurement of pro poor growth distinguishing between a weak and a strong absolute as well as a relative definition. The relevance of each definition depends on the purpose of the analysis as well as the assumptions regarding growthinequality trade-offs. Given the focus of existing measures of pro-poor growth on the income dimension, the second contribution is to present ways to apply the growth incidence curve and the Ravallion-Chen framework of measuring pro-poor growth to non-income indicators. The analysis, which is applied to Bolivia for illustrative purposes, shows that the extension of the propoor growth toolbox to non-income dimensions greatly improves our understanding of the trends in non-income indicators along the entire distribution and thus greatly increases our ability to monitor progress towards the non-income Millennium Development Goals (particularly goals 2-6) and assess the linkages between income and non-income poverty along the entire distribution. This can be of critical importance for poverty monitoring as well as policy interventions including the relative merits of growth versus direct intervention to improve the non?income dimensions of poverty.
Keywords: O12; I32; O46; 330; Wirtschaftswachstum; Einkommensverteilung; Armutspolitik; Bolivien